2011
DOI: 10.1186/1475-2840-10-85
|View full text |Cite
|
Sign up to set email alerts
|

Early and late effects of the DPP-4 inhibitor vildagliptin in a rat model of post-myocardial infarction heart failure

Abstract: BackgroundProgressive remodeling after myocardial infarction (MI) is a leading cause of morbidity and mortality. Recently, glucagon-like peptide (GLP)-1 was shown to have cardioprotective effects, but treatment with GLP-1 is limited by its short half-life. It is rapidly degraded by the enzyme dipeptidyl peptidase-4 (DPP-4), an enzyme which inhibits GLP-1 activity. We hypothesized that the DPP-4 inhibitor vildagliptin will increase levels of GLP-1 and may exert protective effects on cardiac function after MI.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 39 publications
5
84
2
Order By: Relevance
“…The present study demonstrated that exendin-4 mitigates the hypertrophic response and prevented the deposition of collagen content, which was abrogated by depletion of MKK3 and Akt-1. However, in a long-term post-MI cardiac remodeling model, vildagliptin, an inhibitor of DPP4, produced no substantial protective effects on cardiac function or preservations in cardiac remodeling (39). This is likely due to the effects of different pharmacological agents and a different animal model.…”
Section: Discussionmentioning
confidence: 74%
“…The present study demonstrated that exendin-4 mitigates the hypertrophic response and prevented the deposition of collagen content, which was abrogated by depletion of MKK3 and Akt-1. However, in a long-term post-MI cardiac remodeling model, vildagliptin, an inhibitor of DPP4, produced no substantial protective effects on cardiac function or preservations in cardiac remodeling (39). This is likely due to the effects of different pharmacological agents and a different animal model.…”
Section: Discussionmentioning
confidence: 74%
“…Indeed, long-term administration of vildagliptin to normoglycemic rats both prior to and after the induction of myocardial infarction and HF did not attenuate the reduction of LVEF or modify cardiac remodeling (25). Similarly, the administration of saxagliptin to nondiabetic mice with HF secondary to cardiac-specific overexpression of Cre recombinase did not improve ventricular function or modify survival (26).…”
Section: Discussionmentioning
confidence: 99%
“…48,53 However, some studies demonstrated that prolonged availability of intact GLP-1 caused by a DPP-4 inhibitor failed to demonstrate the infarct limiting effect. [26][27][28]54 Moreover, inhibition or reduction of DPP-4 activity using DPP-4 deleted mice or pretreatment with sitagliptin before ischaemia in high fat diet-induced diabetic mice could not reduce the infarct size, but improved the survival rate by activation of cardioprotection kinase such as GSK3β, ANP and Akt. 49 These discrepant results suggest that the different animal models, the duration of ischaemia in the heart models and the minimal dose for a specific time may play a pivotal role in the reduction of the infarct size.…”
Section: Effects Of Dpp-4 Inhibitor On the Infarct Sizementioning
confidence: 99%